Comparison of different methods for measuring the passive film thickness on metals. (20th May 2016) - Benoit, Marie; Bataillon, Christian; Gwinner, Benoit; Miserque, Frédéric; Orazem, Mark E.; Sánchez-Sánchez, Carlos M.; Tribollet, Bernard; Vivier, Vincent
Graphical abstract: Highlights: In situ EIS and ex situ XPS were used for the characterization of zirconium oxide films. The film thicknesses can be obtained from the analysis of a single EIS diagram. A convenient graphical method to extract film properties is proposed. Abstract: In situ electrochemical impedance spectroscopy (EIS) and ex situ X-ray photoelectron spectroscopy (XPS) measurements on electrogenerated zirconium oxide films on zirconium (Zr/ZrO2 ) were used to quantify the oxide film thickness and resistivity profiles through the oxide. The EIS analysis presented here takes advantage of the high-frequency domain at which the constant-phase element (CPE) behavior of the oxide film reverts to a capacitive response and the Cole-Cole representations of the complex capacitance to extract the high-frequency capacitance of the oxide film without reference to the nature of the time-constant distribution within the oxide film. The film thickness of the ZrO2 samples measured from the high-frequency capacitance of EIS were in good agreement with the thickness obtained from XPS. Moreover, the EIS analysis presented is based on the use of the integral solution of the power law model, which allows to obtain in one single EIS experiment, both the film thickness and the resistivity profile in the ZrO2 film. This work suggests a convenient graphical method to extract film properties and serves to validate a key assumption of the power-law model for interpretation of CPE parameters in terms of physical properties.